Consumer Protection in Online Shopping - Saputro, M Susilo Agung; Wardoyo, Nanda Puspitasari; Sofiyana, Nurani; Ramadhani, Shahnata Putri Dwi; Santoso , Aris Prio Agus (Al Makki Publisher, 2024)
Online shopping has become inevitable in today's computer and internet age. To meet customer needs, it was chosen for its convenience, convenience, and accessibility. However, despite such convenience, consumers face risks such as fraud, damaged goods, or non-conformity with product descriptions. Therefore, it is very important to protect customers who shop online legally. This research explores the literature study approach by reviewing literature relevant to legal protection for consumers in online shopping. The purpose of this study is to find problems related to consumer protection in online shopping and provide solutions or suggestions to improve the effectiveness of such legal protection. Customers should be protected when shopping online in the modern era. Preventive and repressive protection is essential to ensure that online transactions are safe and fair. A preventive approach means providing clear and transparent information and adequate technological security to prevent fraud, privacy violations, and other harm. Instead, repressive measures concentrate on applying strict punishment to individuals who commit unlawful acts, such as fraud on the internet. For example, Law Number 8 of 1999 concerning Consumer Protection applies in Indonesia. Government Regulation Number 80 of 2019 concerning Trading Through Electronic Systems also further regulates online purchases. Consumers who shop online may use a variety of settlement settlement mechanisms, such as mediation, arbitration, or consumer settlement settlement companies. Efforts involving various parties are needed to improve legal protection for customers who purchase goods over the internet. The government should increase supervision and enforcement if sellers commit violations. In addition, there needs to be an increase in consumer awareness of their rights when buying goods online.